ANALISIS KARAKTERISTIK ANAK BERKEBUTUHAN KHUSUS (AUTISME) DAN CARA PEMBELAJARAN MENGGUNAKAN MEDIA AUDIO VISUAL PADA ANAK AUTIS - Susanti, Amalia (Jurusan Pendidikan Luar Biasa, 2021)
Autism is an overall developmental disorder that causes problems with behavior, abilities,socialization, and communication. Autistic children have very complex problems that requirespecial attention to help them interact well. This research examines the characteristics of childrenwith special needs in autistic children and how to learn using audio-visual media. The researchmethod used is a qualitative method. The results of research using audio-visual media can beused for learning for autistic children. With audiovisual media, autistic children can communicatethrough movements that have been broadcast via audiovisual media. This can traincommunication in autistic children.